Influence of C groove on energy performance and noise source of a NACA0009 hydrofoil with tip clearance. (October 2020) - Huang, Zhenwei; Huang, Zhenyou; Fan, Honggang
Abstract: In present work, the SST k - ω turbulence model and broadband noise source models are adopted to analyze the effect of the C groove on the energy performance and sources generated by dipoles and quadrupoles around a NACA0009 hydrofoil. Then the correlation mechanism between tip leakage flow (TLF) characteristics and its induced noise is investigated. Results show that the C groove significantly reduces both the area of the primary tip leakage vortex (PTLV) and the turbulent kinetic energy. It can be deduced that the closer the C groove is to the leading edge, the smaller the area of high decibel value of the dipole noise on the surface near the leading edge, but the area of the high decibel value of the dipole noise emitted from the blade tip becomes larger. Furthermore, compared with the original hydrofoil, the C groove reduces the area of quadrupole noise with maximum decrease of 29% for 50 dB. The turbulent kinetic energy in the flow region has a great influence on the quadrupole noise. Highlights: Influence of C groove on energy performance and noise source of a NACA0009 hydrofoil with tip clearance is investigated. The correlation mechanism and internal regulation between tip leakage flow (TLF) characteristics and its induced noise is discussed. The C groove can effectively reduce the quadrupole noise with maximum decrease of 29% for 50 dB.